Nadzór inwestorski w budownictwie: [Investor’s supervision in the construction business] (Studia Prawnicze / The Legal Studies, 1964)
Investor’s supervision is an institution of construction law put into practice in the postwar period as an element of the investment processes in the construction business. It has a universal character in the entire construction business, and its executor on behalf of the investor is a highly qualified person called the investment supervisor.Two kinds of the investment supervisor functions are clearly shown in the legal structure of this institution: according to the provisions of the construction law, the supervisors perform the functions falling within the scope of their activities and having public interest; as investor’s representatives at the construction site, they are obliged to conscientiously ensure that the contractor properly performs obligations under the contract concluded with the investor. Although the investment supervisors do not personally manage the construction process, nevertheless, they play an important role as product quality checkers controlling the quality of materials used at the construction site and the correct execution of the project ordered by the investor.The duties of the investment supervisors are standardized by the construction law, and even their principal cannot release them from these duties. At the same time, the principal may expand the supervisor’s tasks within the power granted. The actions performed by the supervisor within the framework established by law and within their powers entail legal consequences directly for the investor. The legal issues of the investor’s supervision are not limited to the relationship between the investor and the supervisor subordinate to them (based on the employment contract) and the relationship between this supervisor and third parties.Additional legal issues arise in connection with the so-called trusted supervision when an investor who does not have their own technical staff entrusts the performance of the supervisor’s duties to one of the state organizations authorized to accept such mandate; by virtue of Decree No. 141 of the Chairman of the Council of Ministers dated 1958. The Investor’s Supervision Agreement is a contracting agreement (mandatum) where the contractor that is usually a legal entity delegates the supervision duties to its employee who has the skills required by law. According to the provisions of the Code of Obligations on the Contracting Agreement, this supervisor is a deputy contractor who is jointly responsible for the proper performance of the supervision functions.